Development of the Property Marketing Strategy; Case Study at Risma Jihan Akbar Housing Developer, Bekasi - West Java - Sari, Dina Kurnia; Untari, Dhian Tyas; Nursal, M Fadhli (Journal of Economic Development, Environment and People, 2019)
Bekasi is one of the buffer zones that has a fairly high population density, population density will be followed by high demand for property / houses. Based on this background, the research aims to develop a property marketing strategy with a case study on Risma Jihan Akbar (RJA). Mix method was used in this study, by involving consumers and management of RJA as respondents. Processing data using the EFAS/IFAS and Grand Strategy Matrix. The results of the study show that RJA is currently quite good in its marketing strategy, however, the very narrow segmentation causes RJA to be less well known to the public.